2012
DOI: 10.1001/jama.2011.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Antiplatelet Therapy With Cangrelor in Patients Undergoing Cardiac Surgery

Abstract: Context Thienopyridines are among the most widely prescribed medications, but their use can be complicated by the unanticipated need for surgery. Despite increased risk of thrombosis, guidelines recommend discontinuing thienopyridines 5–7 days prior to surgery to minimize bleeding. Objective To evaluate the use of cangrelor, an intravenous, reversible P2Y12 platelet inhibitor for bridging thienopyridine-treated patients to coronary artery bypass grafting (CABG). Design, Setting, and Patients Prospective, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
207
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 420 publications
(216 citation statements)
references
References 40 publications
2
207
1
6
Order By: Relevance
“…The excess dyspnea rates after cangrelor were reported in all 4 randomized trials (BRIDGE [22], CHAMPION-PCI [23], CHAMPION-PLATFORM [24], and finally the largest, CHAMPION-PHOENIX [11]). Each trial consistently revealed two- to three-fold excess rates of dyspnea after cangrelor when compared to placebo, or background clopidogrel.…”
Section: Cangrelormentioning
confidence: 99%
“…The excess dyspnea rates after cangrelor were reported in all 4 randomized trials (BRIDGE [22], CHAMPION-PCI [23], CHAMPION-PLATFORM [24], and finally the largest, CHAMPION-PHOENIX [11]). Each trial consistently revealed two- to three-fold excess rates of dyspnea after cangrelor when compared to placebo, or background clopidogrel.…”
Section: Cangrelormentioning
confidence: 99%
“…Importantly, bridging with a prolonged infusion of cangrelor did not increase major bleeding before surgery, although minor bleedings, largely attributed to ecchymosis at the site of venous puncture, were more commonly documented with cangrelor. 106 The BRIDGE trial therefore supports the hypothesis that bridging with intravenous cangrelor may be a successful strategy to provide adequate platelet P2Y 12 inhibition after thienopyridine discontinuation in patients referred to cardiac surgery. Although this approach has the potential to also be valid in noncardiac surgery, this possibility has still to be proven, given that different noncardiac operations have variable bleeding risk.…”
Section: Bridging Therapymentioning
confidence: 67%
“…This hypothesis has been recently tested in the phase II prospective, randomized, double-blind Maintenance of Platelet inhibition With cangrelor After discontinuation of Thienopyridines in Patients Undergoing surgery (BRIDGE) trial, in which 210 patients with an ACS or treated with a coronary stent and receiving a thienopyridine awaiting CABG surgery were randomly assigned to receive either cangrelor (0.75 μg·kg -1 min -1 ) or placebo for at least 48 hours. 106 The study drug was discontinued 1 to 6 hours before CABG surgery. Aspirin therapy was maintained throughout perioperative period.…”
Section: Bridging Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, platelet inhibition with clopidogrel is irreversible and platelet reactivity is only regained with regeneration of new platelets, which occurs at a rate of ≈10% to 15% per day 16. Conversely, given its very short half‐life, cangrelor can safely be administered up to 1 to 6 hours pre‐CABG without an increase in bleeding, compared with placebo therapy,17 and offers an alternative P2Y12 treatment strategy that avoids the issues of pretreatment with an oral agent.…”
Section: Introductionmentioning
confidence: 99%